The Reported Effects of the Pandemic on the Academic and Developmental Progress of Pupils in Specialist Provisions in England. Using Estimates From School and College Leaders to Determine Differences Between Economically Disadvantaged and Non-economically Disadvantaged Pupils With Special Educational Needs - Webster, Rob; Skipp, Amy; Tyers, Claire (Frontiers in Education, 2022)
This paper addresses an identified gap in research during the COVID-19 pandemic: how the disruption impacted on pupils with special educational needs and disabilities (SEND) attending specialist (i.e., non-mainstream) settings in England. Estimates provided by around 200 special school and college leaders at two timepoints during the pandemic are used to provide overall estimates of the extent to which the pandemic and time spent out of school had on the academic and developmental progress of pupils in these settings. We find that the reported effects are greater than those reported elsewhere for pupils in mainstream settings. In line with research involving the mainstream school population in England, we find that the reported effects on academic and developmental progress were greater for pupils facing economic disadvantage. Additional data from our survey of leaders reveal that the reasons for the reported impact on pupils were: (i) limited access to school or college and the extended periods of non-attendance; (ii) the widespread disruption to the delivery of health and care provision for pupils with complex SEND; (iii) the particular way in which COVID protections and restrictions impacted the curriculum offer in specialist provisions; and (iv) limited digital access, which affected home learning. Looking to post-COVID recovery, special school and college leaders identify an urgent need for tailored support for their communities.